1997
DOI: 10.1006/viro.1997.8796
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Protein–Protein Interactions between the SV40 Capsid Proteins Produced in Insect Cells

Abstract: Soluble SV40 capsid proteins were obtained by expression of the three late genes, VP1, VP2, and VP3, in Sf9 cells using baculovirus expression vectors. Coproduction of the capsid proteins VP1, VP2, and VP3 was achieved by infecting Sf9 cells with the three recombinant baculovirus species at equal multiplicities. All three proteins were found to be localized in the nuclear fraction. Electron microscopy of nuclear extracts of the infected cells showed an abundance of SV40-like capsid structures and heterogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 31 publications
2
62
0
Order By: Relevance
“…Dithiothreitol, PMSF and the protease inhibitor cocktail were added to the buffer immediately before use. 14,15 Nuclear extract concentration was measured using the BCA Protein Assay protocol (Pierce, Rockford, IL). The nuclear extract was kept for more than a year at À201C.…”
Section: Preparation Of Nuclear Extracts From Sf9 Cellsmentioning
confidence: 99%
“…Dithiothreitol, PMSF and the protease inhibitor cocktail were added to the buffer immediately before use. 14,15 Nuclear extract concentration was measured using the BCA Protein Assay protocol (Pierce, Rockford, IL). The nuclear extract was kept for more than a year at À201C.…”
Section: Preparation Of Nuclear Extracts From Sf9 Cellsmentioning
confidence: 99%
“…5B). As a source of VP1 we used nuclear extracts of Sf9 cells infected with a recombinant baculovirus that expresses VP1 (30). The reaction was performed in the presence of double-stranded poly(dI-dC) to compete for the nonspecific binding activity of VP1 (33) and at a low concentration of Sp1, conditions at which Sp1 alone and VP1 alone each bound poorly to the DNA probe (lanes 2 and 3 and lane 7, respectively).…”
Section: Vol 76 2002mentioning
confidence: 99%
“…SV40 virions and pseudovirions can be prepared in vitro. The three capsid proteins VP1, VP2, and VP3, produced as recombinant proteins in insect cells, localize to the nucleus where they assemble spontaneously to form virus-like particles (30). Virus-like particles are capable of incorporating in vitro either SV40 or plasmid DNA, producing infectious particles (29).…”
Section: Vol 76 2002mentioning
confidence: 99%
“…Such structures were originally described for mouse polyoma virus coat protein, VP1, [3][4][5] and it has been shown that a number of different viral coat proteins can behave in a similar manner. [6][7][8][9][10][11][12][13][14][15][16][17] VLPs retain their ability to package DNA. Particles composed of the coat protein packaged with heterologous DNA have been isolated from cells in which the recombinant protein is syn- somes or calcium phosphate precipitates.…”
Section: Introductionmentioning
confidence: 99%